Avaliação epidemiológica dos agravos à saúde relacionados às intoxicações e informações adicionais para o SUS - Nóbrega, Hayanne Oliveira da Silva (2015)
Introduction: Poisoning each year are responsible for the death of half a million people worldwide. Abuse of prescribed and non-prescribed substances and accidents with venomous and non venomous animals reflects on population health and the environment, causing this problem is considered a serious public health problem. Objective: This study aimed to outline the epidemiological profile of toxic events in Paraíba between the years 2009 to 2013. Material and Method: This was a retrospective cross-sectional study that used secondary data collected through the Sinan record, and submitted to statistical analysis association, considering a 95% confidence interval. Results: The results of this study are divided into two articles. The first reports exogenous intoxications and accidents with venomous and non venomous animals which occurred in Paraíba and notified by the only two existing centers in the state, the Service Center and Toxicology Information João Pessoa and Service Center and Toxicology Information Campina Grande. It was observed that the intoxicated Paraíba involved females (56.14%) living in the urban area (87%), aged 20-29 years (20.1%) and intermediate education, with 38.5 % have not completed primary school. The prevailing circumstances in the study were the individual accident (89.5%), suicide attempts (6.4%) and abuse (0.9%), and accidents caused by scorpions (54.9%), Hymenoptera ( 10.3%) and drugs (7.2%). It was observed that the patient seen in Ceatox-CG had approximately five times greater risk of drug intoxication than Ceatox-JP patients (p = 0.000). The same behavior prevailed for snake, pesticides and household cleaning accidents. Scorpion stings are about six times more common in intoxicated attended by Ceatox-JP. Most cases were cured (98.8%). The second article shows poisoning caused by drugs in Ceatox-CG, showing a higher prevalence of females (69.2%), aged 10-19 years (26.6%), and the complete basic education ( 46.3%). These toxic events were more common with attempted suicide (58.5%) and the individual accident (22.8%), whichever the combination therapy (39%) to cause this type of poisoning. Diazepam was the most involved in drug events caused by a single compound. The severity of the cases, stood out as predominantly mild (58.9%), with most evolving to cure (82.8%), with no deaths related to drugs during this period. Conclusion: In Paraíba, poisonings are more prevalent in women aged 20-29 years living in the urban area; and individual accidents, caused mostly by Scorpion stings, with the suicide attempt carried out by the misuse of drugs, are the two main motivational circumstances of the events. Even setting the intoxicated profile in Paraíba, the study shows a marked underreporting of poisonings in the state.